Study of Electrical Transport Properties of Thin Films Used as HTL and as Active Layer in Organic Solar Cells, through Impedance Spectroscopy Measurements - Camilo A. Otalora; Andres F. Loaiza; Gerardo Gordillo (Advances in Materials Science and Engineering)
Impedance spectroscopy (IS) is used for studying the electrical transport properties of thin films used in organic solar cells with structure ITO/HTL/active layer/cathode, where PEDOT:PSS (poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid) and CuPC (tetrasulfonated copper-phthalocyanine) were investigated as HTL (hole transport layer) and P3HT:PCBM (poly-3-hexylthiophene:phenyl-C61-butyric acid methyl ester) blends prepared from mesitylene and chlorobenzene based solutions were studied as active layer and Ag and Al were used as cathode. The study allowed determining the influence of the type of solvent used for the preparation of the active layer as well as the speed at which the solvents are removed on the carriers mobility. The effect of exposing the layer of P3HT to the air on its mobility was also studied. It was established that samples of P3HT and P3HT:PCBM prepared using mesitylene as a solvent have mobility values significantly higher than those prepared from chlorobenzene which is the solvent most frequently used. It was also determined that the mobility of carriers in P3HT films strongly decreases when this sample is exposed to air. In addition, it was found that the electrical properties of P3HT:PCBM thin films can be improved by removing the solvent slowly which is achieved by increasing the pressure inside the system of spin-coating during the film growth.